A methods engineering study of Recon Printing Press, Inc. - Villanueva, Earl (College of Engineering, 1996)
The study aims to improve the productivity of Recon Printing Press, Inc. by improving the materials/products flow of the company under study. Data were gathered through plant visits of the printing press' building located at 324 Celery Rd., FTI Complex, Taguig. Using the Stream Analysis Chart, it was found that there were two major problems in the system. There was poor record keeping and inefficient layout. The forms of the company were also studied and its flow by using the forms distribution chart. Several alternatives were presented to address the problems. The travel chart and relationship chart were used to design a more efficient layout. Also, shelves and platforms were designed to hold inventory materials and organize space utilization. The design of several forms (Job Order, Invoice, and Requisition Slip) were altered to make it easier to accomplish and more readable. Unnecessary copies of a form (Job Order) were eliminated. The alternatives were evaluated and ranked to determine which one should be prioritized. A table summarizing the recommendations, its cost, benefits and schedule of implementation are presented at the end of the study.